Liquid Biopsy and Radiological Response Predict Outcomes Following Discontinuation of Targeted Therapy in Patients with BRAF Mutated Melanoma. (21st September 2021) - Di Guardo, Lorenza; Randon, Giovanni; Corti, Francesca; Vallacchi, Viviana; Raimondi, Alessandra; Fucà, Giovanni; Bini, Marta; Maurichi, Andrea; Patuzzo, Roberto; Gallino, Gianfrancesco; Mattavelli, Ilaria; Ruggeri, Roberta; et al.
Abstract: Background: Outcomes of patients with metastatic melanoma discontinuing BRAF‐targeted therapy for cumulative toxicity after sustained response are unknown. Materials and Methods: This retrospective case series analysis conducted at a single Cancer Center in Italy included patients with BRAF mutated metastatic melanoma treated with a BRAF inhibitor as a single agent or in combination with a MEK inhibitor between June 1, 2011 and January 1, 2020 and interrupted treatment due to cumulative toxicity after achieving complete response (CR) or long‐lasting partial response (PR; i.e. >12 months). Results: We included 24 patients with a median treatment duration of 59.4 months (95% confidence interval [CI], 55.4–63.4; range, 12–88). CR and PR were achieved in 71% and 29% of patients, respectively. At a median follow‐up after treatment discontinuation of 37.8 months (95% CI, 33.7–41.9), the 12‐month progression‐free survival after discontinuation (dPFS) rate was 70.8% (95% CI 54.8–91.6) and 24‐month dPFS rate was 58.3% (95% CI, 41.6–81.8). Baseline patient and tumor characteristics as well as treatment duration and best response did not significantly impact on dPFS. Patients with CR and negative circulating tumor DNA (ctDNA) at time of discontinuation had a significantly improved dPFS compared with patients with either radiological residual disease or ctDNA positivity ( p = .007). No patient in CR with undetectable ctDNA experienced progression. Conclusion: The risk of progression is high even in patients with sustained sensitivity to BRAF/MEK inhibitors. Integration of liquid biopsy in clinical trials investigating the optimal management of patients with sustained sensitivity to BRAF/MEK inhibitors is warranted. Implications for Practice: Outcomes of patients with metastatic melanoma discontinuing BRAF‐targeted therapy for cumulative toxicity are unknown. This study analyzed patients with sustained responses (median treatment duration 59.4 months). Twelve‐ and 24‐month progression‐free survival following discontinuation were 70.8% and 58.3%, respectively. Complete response and negative circulating tumor DNA at time of discontinuation are promising prognostic biomarkers in this setting. Abstract : This article reports clinical outcomes of patients with metastatic melanoma treated with BRAF/MEK inhibitors who interrupted the treatment after achieving a long‐lasting objective response, exploring the role of circulating tumor DNA assessed at time of discontinuation as a biomarker for post‐discontinuation progression‐free survival.